Gendered Mobility Constraints in Semi-Formal Urban Transport Systems: An Empirical Study of Para-Transit in Lahore - Fatima, Manahal; Nasir, Minahil; Iqbal, Muzaffar Aziz (Journal of Art, Architecture and Built Environment, 2025)
The findings of this study disclose a very harassing environment where a significant majority reported frequent experiences of harassment in the forms of verbal intimidation and physical intimidation both at the time of waiting, while on travel, and upon arrival. These safety concerns further worsen with poorly maintained and male-dominated waiting areas, coupled with a deep-seated institutional lack of trust. The paper concludes that such barriers considerably reduce the mobility of women to access education, employment, and civic engagement and thereby undermine the urban autonomy of women. It argues that only an integrated intervention-a regulatory, infrastructural design and technological solution, along with deep-seated social attitudes-can bring about change in paratransit from a source of risk to a pillar for equitable mobility through participatory, gender-responsive planning.